Canzoni d'attore. Musica, performance e (nuovi) media nel film "Lo chiamavano Jeeg Robot" (2015) (Schermi. Storie e culture del cinema e dei media in Italia, 2020)
The article addresses the role of music and media in Gabriele Mainetti’s film “Lo chiamavano Jeeg Robot” (“They Call Me Jeeg”, 2015). In so doing it relies on an interdisciplinary framework combining musicology, performance studies and media studies. I start by considering the production, circulation and reception of pre-existing music used in the film, then I shift to the dramaturgy of the film in relation to both its original music and compiled soundtrack. While the latter, including Italian songs from the period 1978-1982, is referred to the character of Fabio Cannizzaro aka “lo Zingaro” (Luca Marinelli), the former unwinds alongside the evolving psychology of the protagonist Enzo Ceccotti (Claudio Santamaria). The use of songs in the film incorporates and expresses multiple dimensions of performance: the actor’s performance, the villain’s criminal and musical persona, and the performativity of the media, which the film explicitly problematizes. This allows to frame the film and its compilation soundtrack in a wider perspective, reflecting upon the Italian media system of the 1980s and its relation with the present pervasiveness of new digital media.